Quelle Europe pour les cartographes des XVIe et XVIIe siècles ? - Monique Pelletier (Belgeo, 2008)
The engraved Europe maps of 16th and 17th centuries were part of the geography also expressed by texts and images – views and maps of cities, inhabitant clothes –, which were useful complements. They were mainly intended for history readers anxious to locate studied events. They were also used by those admiring the marvels of the created world and by tradesmen willing to expand their activities in and beyond Europe. They were supported by economic and political powers because they were providing useful information. Their geographic and aesthetic qualities were improving, but maps finished up stabilizing, always offering the same data in editions which only differed by imprint dates. In spite of this failing, the accompanying texts and illustrations were remaining good guides on Europe perception by people living in the 16th and 17th centuries.